What determines Enset (Ensete ventricosum) production and its contribution to household income? Empirical evidence from Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2021)
Enset production in Ethiopia is seemingly limited to only consumption-based production and most of producers supplied small amounts of products to the market. This study was conducted with main objective of assessing factors affecting market participation of enset producers in Chena district in southwestern Ethiopia. Two-stage sampling technique was employed to select 101 representative enset producer households. Both primary and secondary data sources were used to gather necessary data for attaining specific objectives of the study. Both descriptive statistics and econometric model were used to analyze the collected data. A Heckman two stage model was employed to analyze the factors affecting households’ decision in market participation in sale of enset products and the amount of gross income earned. Econometric model analysis result showed that; sex of household head, education level, livestock owned, a distance from nearest market center, enset plantation size, and transport access were found to be significant in affecting the probability of market participation decision. In addition, education level, family size, distance from market center, enset plantation, and transport access affected the amount of gross income earned from sale of different enset products. The result suggests the need for stakeholders’ involvement to enable market-oriented production of crop to encourage farmers for better crop production and market supply to have increased amount of income and proper utilization of the crop.Int. J. Agril. Res. Innov. Tech. 11(1): 17-25, June 2021